Diastereo- and enantioselective cyclopropanation of alkyenyl fluorides with benzyl diazoarylacetates. Issue 14 (1st April 2015) - Su, Yan; Bai, Miao; Qiao, Jin-Bao; Li, Xiao-Jing; Li, Rui; Tu, Yong-Qiang; Gu, Peiming
Graphical abstract: Abstract: A catalytic diastereo- and enantiocontrolled preparation of cis -β-fluorocyclopropane carboxylates through the Rh-catalyzed cyclopropanation of alkenyl fluorides with diazoarylacetates has been realized. Rh2 ( S -DOSP)4 and benzyl diazoarylacetates were found to be beneficial to the cyclopropanation with high diastereoselectivity. Thirteen cis -β-fluorocyclopropane carboxylates were prepared in hexane at 0 °C with good to excellent yields. The enantiomeric excess was up to 97%, and the diastereomer ratio was up to 95:5.